Model System Dynamics Infrastruktur BTS Ramah Lingkungan Daerah Rural untuk Optimalisasi Perhitungan ARPU - Sardjono, Wahyu (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Green Base transceiver station (BTS) or known as remote BTS is a special BTS with IP technology-based that has a small capacity and takes low power consumption with standard features suitable for use in rural areas. BTS utilizes 100% solar energy as a source of energy. The infrastructure Green BTS is composed of high-tech devices which is able to save energy, environmentally friendly, small and lightweight. The high rate service calls and SMS on green BTS is caused by the absence of competition telecom operators at a site. The solution to this  problem needs to be done with system dynamics modeling approach with the aim to establish causality (cause and effect) between the variables. The standard target of model pattern which has been changed on system dynamics can be used to demonstrate the behavior of the model between the number of subscribers, the availability of network capacity and ARPU (average revenue per user) on the Green BTS site. On the changed standard target model, the actual revenue is placed as the actual event, the target revenue is as a target; the difference between the actual and target revenue is as gap, gap changes are as the pressure on the target and the corrective action taken against revenue as a corrective action. Based on simulation results, the standard model change targets can be developed by adding two negative loops (balancing loop) as an alternative solution towards the achievement of revenue targets that have been set.